(untitled) (Development Service Industry Management, 2024)
The study updates the issue of guaranteeing the economic stability of domestic economic entities in the conditions of a full-scale war. Therefore, the purpose of this publication is the substantiation of the principles, as well as the definition of the system of criteria for making management decisions in the field of ensuring the economic stability of business entities in conditions of critical instability. It is shown that sustainability is a category derived from the economic security of business entities. Therefore, its basic provisions are based on security. At the same time, it has its own specificity, mainly due to the fact that stability is the ability to maintain one’s condition on a permanent basis (regardless of the deterioration of external or internal environmental conditions), while security assumes certain relaxations, but only up to a critical level, at which bankruptcy follows. Therefore, stability makes it possible to guarantee stronger and more stable positions, which is more important in the conditions of a full-scale war, in other words, a critically high level of instability. On this basis, the principles are defined, as well as the criteria for making managerial decisions in the field of management of the economic stability of economic entities are substantiated. It has been established that the leading principles in the field of quality management of the economic stability of economic entities in conditions of critical instability should include: Identification and prevention of challenges and threats; complexity and systematicity; planning and reporting; constancy; preventive measures against challenges. It has been proven that the main areas in which certain decisions affecting the preservation and strengthening of the economic stability of Ukrainian enterprises in conditions of critical instability are initiated are the issues of business organization & stability management, economic efficiency vs. sustainability, financial stability vs. investment projects, market & marketing, accounting & security.